"You always have a high sugar if you don't communicate": A qualitative secondary analysis of 'Diabetes Together' process evaluation data from couples in South Africa. - Lucy Lynch; Myrna van Pinxteren; Peter Delobelle; Naomi Levitt; Buyelwa Majikela-Dlangamandla; Kate Greenwell; Nuala McGrath (PLOS Global Public Health)
Type 2 Diabetes Mellitus (T2D) can negatively impact relationships which may affect health and disease management. This can be moderated by positive communication between partners. Our aims were first, to identify ways in which couples' communication and T2D impact each other. Second, we aimed to explore how improving couples' communication may enhance self-management for people living with T2D (PLWD) and their partners in South Africa. We conducted secondary data analysis of qualitative interview and focus group data from an intervention pilot study designed to improve T2D self-management - 'Diabetes Together'. 14 PLWD and their partners took part in two diabetes self-management workshops, including communication skills training, and were offered two couples counselling sessions. Inductive thematic and dyadic analysis explored how T2D and couples' communication were connected, and how participants perceived the impact of couples' communication skills training. Findings were compared to data collected from qualitative interviews with intervention-naive participants. We generated four themes linking couples' communication and T2D: tone of discussions; listening; openness; and being informed about T2D. Participants described that T2D can create negative moods and stress (both from the disease and its management) and this can make communication challenging. They reported that negative communication styles can create stress worsening T2D and making it harder to manage. Participants felt that positive communication could ease stress, enable problem-solving and support behaviour change, which may improve T2D management. Couples reported that communication skills training helped them to address communication-related issues in their relationships. This included managing negative moods, changing communication styles and developing skills to discuss, listen and collaborate on improving T2D self-management. PLWD and their partners perceived that T2D and couples' communication can affect one another positively and negatively. Equipping couples with effective communication skills may empower them to manage T2D more effectively.